Lung cancer in renal transplant recipients: A case-control study. (September 2017) - Rousseau-Gazaniol, Claire; Fraboulet, Séverine; Couderc, Louis-Jean; Kreis, Henri; Borie, Raphaël; Tricot, Leila; Anglicheau, Dany; Martinez, Frank; Doubre, Hélène; Bonnette, Pierre; Mellot, François; Massiani, Marie-Ange; et al.
Highlights: Incidence of LC in KTRs was 1.89/1000 person-years during the period 2008–2012. Despite routine diagnosis in 40% of cases, most patients had advanced lung cancer. Squamous cells carcinomas were over-represented in KTRs. Management of lung cancer was not different between KTRs and controls. Despite more infection-induced admissions in KTRs, overall survival was not different. Abstract: Introduction: Solid organ transplant patients are at heightened risk of several cancers compared to the general population. Secondary to a higher number of procedures and better survival after transplantation, cancer is a rising health concern in this situation. Limited data exist for lung cancer (LC) after renal transplantation. We report here the most important series of renal transplant recipients with lung cancer. Methods: Retrospective study of all cases of LC diagnosed in three French Renal Transplant Units from 2003 to 2012. A control group consisted of non-transplant patients with LC matched with the cases for age (<30; 30–50; 50–65; >65 years), gender and diagnosis date. We recruited two controls for each case. Results: Thirty patients (median age 60 years; range 29–85; male/female ratio 80/20%) with LC were analysed. LC incidence was 1.89/1000 person-years over the period 2008–2012. All patients were former or active smokers (median 30 pack-years). Transplanted patients had significantly more comorbidities, mainly cardiovascular disease. The median interval of time from kidney transplantation (KT) to diagnosis of LC was 7 years (range 0.5–47 years). LC was incidentally diagnosed in 40%. Most patients (70%) had advanced LC (stage III or IV) disease. Stage of LC at diagnosis was similar in cases and controls. Surgery and chemotherapy were proposed to the same proportion of patients. In cases, mortality was cancer related in 87% and median survival time after diagnosis was 24 months. Survival was not significantly different between the 2 groups. Conclusion: Despite frequent medical and radiological examinations, diagnosis of LC is usually made at an advanced stage and the overall prognosis remains poor.